B cell targeted therapy for immunoglobulin G4-related disease. Issue 4 (2nd October 2021) - Yamamoto, Motohisa
Abstract: Glucocorticoids are the first-line drug for the remission induction therapy of immunoglobulin (Ig) G4-related disease. Achieving drug-free remission using glucocorticoids alone is difficult, however, and many patients require maintenance therapy with glucocorticoids and immunosuppressants. Studies have recently found that the number of peripheral memory B cells and plasmablasts is increased in IgG4-related disease and have indicated the efficacy of rituximab, which, in remission induction therapy, rapidly reduces serum IgG4 levels and has the tapering effect of glucocorticoids. Rituximab has been shown to reduce the risk of relapse more than oral immunosuppressants such as azathioprine. However, maintaining drug-free remission is difficult with a single course of rituximab alone, and many cases require maintenance therapy with rituximab. This article outlines the potential of B-cell targeted therapy, focusing on the efficacy, and safety of rituximab for IgG4-related disease.